Protein Arcs May Form Stable Pores in Lipid Membranes - Prieto, Lidia (The Biophysical Society, 2014)
Electron microscopy and atomic force microscopy images of cholesterol-dependent cytolysins and related proteins that form large pores in lipid membranes have revealed the presence of incomplete rings, or arcs. Some evidence indicates that these arcs are inserted into the membrane and induce membrane leakage, but other experiments seem to refute that. Could such pores, only partially lined by protein, be kinetically and thermodynamically stable? How would the lipids be structured in such a pore? Using the antimicrobial peptide protegrin-1 as a model, we test the stability of pores only partially lined by peptide using all-atom molecular dynamics simulations in POPC and POPE/POPG membranes. The data show that, whereas pure lipid pores close rapidly, pores partially lined by protegrin arcs are stable for at least 300 ns. Estimates of the thermodynamic stability of these arcs using line tension data and implicit solvent calculations show that these arcs can be marginally stable in both zwitterionic and anionic membranes. Arcs provide an explanation for the observed ion selectivity in protegrin electrophysiology experiments and could possibly be involved in other membrane permeabilization processes where lipids are thought to participate, such as those induced by antimicrobial peptides and colicins, as well as the Bax apoptotic pore.